'The precious material': obtaining human fetal bodies for an embryological collection at Uppsala University, ca 1890–1930. (15th March 2022) - Franzén, Helena
ABSTRACT: In the late nineteenth century, anatomists at Uppsala University took an interest in embryology, that is, fetal development from conception to birth. In order to conduct embryological research, fetal bodies from all stages of development were needed, but difficult to obtain. By building connections with medical professionals – such as midwives, physicians, and obstetrician-gynaecologists – who had access to pregnant and labouring women, the anatomists at Uppsala University were able to assemble the raw material for their research. However, the various professions involved, and the female patients, had different understandings of what fetal bodies meant and how to manage them. By exploring three contexts of collecting fetal bodies – miscarriages, surgeries to address ectopic pregnancy, and the birth of deviant bodies – this study draws attention to the social processes of knowledge production. It highlights the plethora of meanings ascribed to fetal bodies; underscores that these meanings were underpinned, as well as affected, by understandings of pregnancy; and argues that medical knowledge of reproduction was produced in the dynamic relations between the embryological collection and medical practice.